PSYCHOSOCIAL DEPRIVATION OF PRE-SCHOOL CHILDREN - V.C., Onyeike; Agbankwuru, Chikwe (European Scientific Journal, ESJ, 2012)
This study investigated psychosocial deprivations among nursery school pupils in Ezinihitte Local Government Area of Imo State, Nigeria. The sample consist of 150 pupils who were drawn through proportionate random sampling technique from 6 public nursery schools in the area of study. Four research questions were posed and data for their investigation were collected using copies of researchers developed questionnaire called Psychosocial Deprivation and Pre-school Assessment Questionnaire (PDPSAQ). The test – restest reliability co-efficient of this instrument within an interval of two weeks is 0.89. The teachers interpreted the items in the questionnaire to the pupils and scored their responses. All the research questions were answered with simple percentage test statistic and the results show that nursery school pupils suffer psychological and social deprivations. It also shows that girls suffer more psychological and social deprivations than the boys. These results were discussed and some useful recommendations made one of these is that parents/guardians should desist from differential socialization of male and female children.